Endocrine actions of IFNT during early ruminant pregnancy - Romero, Jared Jerome, author; Hansen, Thomas R., advisor; Van Campen, Hana, committee member; Bouma, Gerrit J., committee member; Nett, Terry M., committee member; Davis, John S., committee member (Colorado State University. Libraries, 2013)
The mechanisms of how conceptus-derived interferon tau (IFNT) induces interferon stimulated genes (ISGs) and cell survival genes through endocrine action that contributes to resistance of the Corpus Lutum (CL) to prostaglandin Fα (PGF) and the maintenance of early pregnancy in sheep were examined. Using microarray screens, several genes were identified in the CL to be significantly up-regulated [ISG15 and myxovirus (influenza virus) Resistance 1; MX1], maintained [interleukin 6; IL-6, Pentraxin, long 3; PTX3, luteinizing hormone receptor; LHR, and vascular endothelial growth factor; VEGF] or down-regulated [serpin peptidase inhibitor, clade E; SERPINE1, thrombospondin 1; THBS1] in response to pregnancy and luteolysis. These studies in the CL were expanded to other tissues (endometrium, liver, uterine vein tissue) and bodily fluids (blood and histotroph) to identify other endocrine actions of IFNT and other conceptus secretory products that could be used to explain mechanisms of establishment and maintenance of pregnancy and to be used as blood markers for pregnancy status. The extensive examination of key genes described herein that were differentially regulated during Days 12-15 of the estrous cycle and pregnancy in ewes is novel. The experiments are the first to examine extensive temporal regulation of key genes associated with luteolysis such as estrogen receptor (ESR1), oxytocin receptor (OXTR), prostaglandin transporter (SCLO2A1) and caspase 3 (CASP3); and luteotrophic-cell survival genes such as Phosphoinositide-3-Kinase/V-Akt Murine Thymoma Viral Oncogene (PI3K/AKT) and ISGS. To identify novel markers of pregnancy status and establishment of pregnancy, global mass spectroscopy was used for analysis of the proteome and metabolome. From this extensive analysis, 14 proteins/metabolites were more extensively examined: Acetyl-carnitine, Carnitine, Ecdysteroids, N-acetyldileucine, Valine, Collagen, Type I, Alpha 1 (COL1A1), Collagen, Type I, Alpha2, (COL1A2) Annexin A1, Annexin A2, Annexin A5, IFNT, Trophoblast Kunitz Domain Protein 1 (TDKP1) Profilin 1 (PFN1) and S100 Calcium-Binding Protein A11 (S100a11). The critical roles for these metabolites and proteins are discussed in context of the establishment and survival of a pregnancy. To confirm that IFNT has an endocrine role during early pregnancy, a highly specific [no cross-reaction with Interferon alpha, beta and gamma (IFNA, IFNB or IFNG)] and sensitive (23.95 pg/ml in serum) IFNT radioimmunoassay was validated herein. IFNT could be detected using this refined assay in ewes from Days 13-16 of pregnancy in histotroph, in uterine vein serum by Day 15-16 of pregnancy and as early as Day 19 of pregnancy in tail blood from pregnant dairy cows. Through these studies it was determined that Day 14 is a very pivotal day for the establishment of pregnancy in ewes. Detection of IFNT in tail blood of pregnant cows on Day 19 provides further evidence for the endocrine action and systemic release of IFNT during pregnancy in ruminants.
Keywords: pregnancy; ruminants; Corpus Luteum; IFNT; luteolysis; reproduction